The Effect of Additional Employee Income Allowance (TPP) and Islamic Organizational Culture on the Quality of Internal Services at Sub-District Offices in Tulang Bawang Regency - Rizal Ferdiansyah; Finny Ligery; Muhamad Agus Mushodiq; Ahmad Muklisin; Muhammad Yusuf; Subandi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the effect of Additional Employee Income (TPP) and Islamic Organizational Culture on Internal Service Quality in sub-district offices throughout Tulang Bawang Regency. The background of this research is based on the importance of improving public service quality, which is determined not only by external services delivered to the community but also by the quality of internal services among employees within governmental organizations. The provision of TPP as a performance-based incentive instrument and the strengthening of Islamic organizational values are considered strategic factors in enhancing employees’ motivation, discipline, and professionalism. This research employed a quantitative approach using a survey method. The population consisted of all Civil Servants (ASN) in sub-district offices across Tulang Bawang Regency, with a sample size of 134 respondents using stratified sampling techniques. Data were collected through questionnaires using a Likert scale and analyzed using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach. The results indicate that Additional Employee Income (TPP) has a positive and significant effect on Internal Service Quality. Likewise, Islamic Organizational Culture has a positive and significant influence on Internal Service Quality. These findings suggest that improving employee welfare through fair and performance-based financial incentives, combined with the internalization of Islamic values such as trustworthiness, honesty, responsibility, and professionalism, can significantly strengthen internal service quality within governmental organizations. This study implies that the synergy between material and non-material factors is essential for enhancing organizational performance and sustainable public service quality.